Catalysts from earth abundant materials in a scalable, stand-alone photovoltaic-electrochemical module for solar water splitting. Issue 33 (31st July 2018) - Welter, K.; Hamzelui, N.; Smirnov, V.; Becker, J.-P.; Jaegermann, W.; Finger, F.
Abstract : Stable performance of a solar water splitting device with an area of 64 cm 2 and catalysts from earth abundant materials. Abstract : We report on the preparation and performance of catalysts from earth abundant materials and their implementation in a stand-alone photovoltaic-electrochemical (PV-EC) module with 64 cm 2 active area. NiFeO X as the oxygen evolution reaction catalyst and NiMo as the hydrogen evolution reaction catalyst were electrodeposited on nickel sheets. We compare the NiFeO X /NiMo catalysts to a noble metal catalyst system consisting of IrO X and Pt regarding their potential for upscaling to large areas and their application and performance in the PV-EC module with a triple junction thin film silicon based solar cell. Additionally, we present long-term stability measurements of the catalyst systems (i) NiMo/NiFeO X and (ii) Ni/Ni under simulated day-night cycles. Overall, we show the feasibility of using earth abundant catalysts in an upscaled stand-alone PV-EC module. The NiMo/NiFeO X catalyst pair outperforms the precious metal catalysts with a solar-to-hydrogen efficiency of η STH (NiMo/NiFeO X ) = 5.1% ( η STH (Pt/IrO X ) = 4.8%) and shows an excellent long-term stability in the simulated day-night cycles.